2019
DOI: 10.1155/2019/7459457
|View full text |Cite
|
Sign up to set email alerts
|

Wirelessly Powered Endoscopically Implantable Devices into the Submucosa as the Possible Treatment of Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux disease (GERD) is a rather common disease with a prevalence reaching up to 10 or 20% in the western world. The most specific symptoms which point to the diagnosis of GERD are feelings of heartburn and the regurgitation of acidic stomach contents into the esophagus. However, a certain number of patients do not respond to standard therapy, and in these cases, it is necessary to resort to other treatment methods, such as laparoscopic fundoplication or electrostimulation of the lower esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…All patients had an increase in LES pressure after the procedure ( 58 ) ( Table 4 ). There is also a recent porcine study using battery-device for electrical stimulation but no human studies available yet ( 59 ). Given that most human studies are available from laparoscopic studies, further large human studies with endoscopic implantation of devices are needed.…”
Section: Advances In Endoscopic Treatments For Gerdmentioning
confidence: 99%
“…All patients had an increase in LES pressure after the procedure ( 58 ) ( Table 4 ). There is also a recent porcine study using battery-device for electrical stimulation but no human studies available yet ( 59 ). Given that most human studies are available from laparoscopic studies, further large human studies with endoscopic implantation of devices are needed.…”
Section: Advances In Endoscopic Treatments For Gerdmentioning
confidence: 99%
“…Further advances include the endoscopic placement of a battery‐less stimulator. As only porcine models have been used to test these battery‐less devices, human studies are needed before this can be considered a viable treatment option 12 . In the coming years, electrical stimulation of the LES is a potential technology that could be utilized to treat patients with GERD.…”
Section: Electrical Stimulation Of the Lesmentioning
confidence: 99%
“…The device was shown to reduce symptom scores and acid exposure time in patients who were partial responders to PPI, although this was only an uncontrolled before-after study [110]; bowel perforation, lead erosion and dysphagia have been reported postprocedure. A miniature device has been developed that can be implanted by an endoscope into the submucosal pocket near the lower oesophageal sphincter which is minimally invasive [111]. Overall, the exact efficacy of neurostimulation in refractory GERD is uncertain but may represent a future alternative in clinical practice.…”
Section: Oesophageal Neurostimulationmentioning
confidence: 99%